Keeping A Harmonious Relationship With Elderly Family Members Who Are Not Living Together Through Communication - Sahara Dwi Yunita; Shinta Doriza; Maya Oktaviani (Eligible : Journal of Social Sciences, 2022)
Communication is the most important thing in human life and must be maintained effectiveness. Communication has a role to see how harmonious a family is. Over time there will be a transfer of responsibility in caring for the elderly in a family due to busy work or no time to take care of the elderly. The purpose of the study was to find out the relationship of elderly harmony through communication without the presence of one of the members who are not at home. Research uses a descriptive qualitative research approach. Research informants as many as 5 elderly in Jakarta who have one of the family members are not at home. Data collection techniques use the process of interviewing, observation, and documentation. Data analysis techniques use interactive models, namely: data reduction, data presentation, and conclusion/verification withdrawal. The results showed that communication carried out smoothly despite the busyness of work or taking care of children and the willingness of a good time. Aspects of communication have time and togetherness in the family seen in all respondents except aspects of listening and honesty.